Surgery for local recurrence or distant metastases in patients aged 75 years or older - Lehnert, Thomas; Pfitzenmaier, Jesco; Hinz, Ulf; Herfarth, Christian (European journal of surgical oncology, 1998)
Between 1982 and 1997, a total of 105 patients aged 75 years or older (median age 78 years) underwent surgical treatment for recurrent solid tumours. The most frequent primary tumours were melanoma, colorectal carcinoma and breast cancer. Sixty-one patients had complete removal of recurrent tumour. Post-operative mortality was 3.8% (four of 105 patients). The median hospital stay was 16 days and the post-operative hospital stay was 10 days. At a median follow-up of 57 months, 77 patients had died. Twenty one patients died of causes unrelated to the tumour. The overall survival of 105 patients was 35% at 3 years and 27% at 5 years. Following R0 resection, 5-year survival was 43% (n = 61) and in the absence of post-operative complications even reached 50% (n = 47). Survival correlated with completeness of tumour resection (P<0.0001) and post-operative complications (P = 0.021). No significant correlation could be established between survival and age, ASA score, blood replacement, primary tumour location or sex. Elderly patients presenting with recurrent tumour should be evaluated for surgical resection. If tumour removal is complete and post-operative complications are avoided, a 5-year survival rate of over 40% may be expected.
Elektronische Reproduktion der Druck-Ausgabe 29 Oktober 2004
Gesehen am 03.11.2025